Coping mechanisms of Japanese team sport athletes in response to injury - Geisler, G.; Razavi, S.; Kerr, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Injury in competitive sport can jeopardize an athlete`s confidence, self-esteem, and sense of identity (Brown, 2005). Research into corresponding coping mechanisms has centered largely on problem-focused and emotion-focused strategies, but the integrated model of Wiese-Bjornstal, Smith, Shaffer, and Morrey (1998) also lists ethnicity and various social influences as factors in the psychological response to injury and rehabilitation. Therefore, the aim of this study was to examine the coping mechanisms of non-Western (Japanese) team sport athletes after debilitating sports injuries. Methods: The participants were 12 Japanese intercollegiate athletes who competed in soccer, rugby, baseball, and American football. Each had sustained a serious injury and was currently involved in a physical rehabilitation program. Data were collected through semi-structured interviews and responses were transcribed verbatim. They were then analyzed via content analysis, which identified various meaning units that were categorized into higher order themes. Results: All of the athletes used a near-equal share of problem-focused and emotion-focused coping strategies. The most common methods involved physical interventions and distractions, such as swinging a bat while sitting, picking up balls for the pitcher, and participating as much as possible in team warm-up and cool-down activities. To maintain spirits and a sense of accomplishment, players also tried to stay active by doing core conditioning and training uninjured parts of the body. Lastly, many players reported a total reliance on their trainers as a coping resource. Discussion: A number of culturally-derived cognitions could be gleaned from the research data. To illustrate, beliefs that `getting injured prevented me from contributing to the team,` `the trainers` devotion to my recovery kept me from giving up," and "the trainer has been working to treat me so I have to make progress" reflect the collectivistic nature of Japanese society and the hierarchical power dynamics within groups (Markus & Kitayama, 1991), including those of sports teams. Accordingly, the findings are compared and contrasted with the extant literature for Western athletes, and implications for future research and practice are addressed.